Ricardo Palma: forjador de la conciencia socio-histórica del Perú - Arroyo Laguna, Eduardo (2018)
Ricardo Palma’s life is one of the most passionate of our history. He was an intellectual besides a political, an action man. During his life he wrote poetry, journalism, theater, chronicle and Traditions, becoming in the social-historical consciousness of Perú.